High COL10A1 expression potentially contributes to poor outcomes in gastric cancer with the help of LEF1 and Wnt2. Issue 9 (5th August 2022) - Zhang, Miaozun; Jin, Ming; Gao, Zhiqiang; Yu, Weiming; Zhang, Wei
Abstract: Background: COL10A1 is a secreted, short‐chain collagen found in several types of cancer. Studies have shown that COL10A1 aberrant expression is considered an oncogenic factor. However, its underlying mechanisms and regulation of gastric cancer remain undefined. Methods: The data on the expression of COL10A1, clinicopathological characteristics, and outcome of patients with GC were obtained from The Cancer Genome Atlas. The ALGGEN‐PROMO database defined the related transcription factors. Quantitative real‐time reverse transcription‐polymerase chain reaction and western blotting analysis were used to identify the differential expression levels of COL10A1 and related transcription factors. Results: We found that high COL10A1 expression is an independent risk factor for gastric cancer. Upregulation of LEF1 and Wnt2 was also observed in gastric cancer, suggesting a potential correlation between LEF1/COL10A1 regulation in the Wnt2 signaling pathway. Conclusion: High COL10A1 expression may contribute to poor outcomes via upregulation of LEF1 and Wnt2 in gastric cancer. Abstract : We performed bioinformatic analysis and experiments to identify the differential expression levels of aimed molecules. In addition, we found that high COL10A1 expression is an independent risk factor for GC. Upregulation of LEF1 and Wnt2 was also observed in GC, suggesting a potential correlation between LEF1/COL10A1 regulation in the Wnt2 signaling pathway.